Upaya Hukum Banding Terhadap Putusan Verstek Yang Diajukan Oleh Pihak Tergugat Dikaitkan Dengan Asas Kepastian Hukum Dalam Tinjauan HIR/RBG - Sherly Ayuna Putri; Achmad Syauqi Nugraha (Departemen Hukum Perdata, 2020)
The verdict of Verstek is the ruling that where the defendant, although called legitimately, does not come on a given day, and does not tell others to be facing his deputy, the claim is accepted with a decision without the presence (Verstek). Resistance is a legal effort against the verdict that was dropped outside the presence of the defendant. Essentially the resistance was provided for the defendant who (in general) was defeated. The Verzet is governed in article 125 paragraph (3) and 129 HIR, article 149 clause (3) Jo. 153 RBg. The research method which is conducted in this study is normative juridical research that emphasizes on the science of law and conduct an inventory of positive law relating to the effectiveness of statutory regulations in the ﬁ eld of legal and descriptive analytical describing and analyzing the problems based on the legislation governing the law of civil proceedings regarding the legal efforts of Verstek decision. Based on the results of the study obtained ﬁ rst problem of Verstek decision to be ﬁ led by the defendant on the decision of the District Court of Bale Bandung Case Number: 37/PDT. G/2018/PN. BLB and the state court ruling of the Simalungun case number: 36/PDT. G/2013/PN. LICENSE does not conform to the norm in article 125 HIR and section 149 RBg. The two remedies that can be done by the plaintiff or the appeal is to apply for the appeal with the reasons set out in article 30 paragraph (1) of Law No. 5 of 2004 concerning the Supreme Court, among other things relating to the judge is not authorized or exceeds the limits of authority and or wrong in implementing or violating applicable laws.